Mechanism of White Matter Injury and Promising Therapeutic Strategies of MSCs After Intracerebral Hemorrhage - Li, Jing; Xiao, Linglong; He, Dian; Luo, Yunhao; Sun, Haitao (Frontiers in Aging Neuroscience, 2021)
Intracerebral hemorrhage (ICH) is the most fatal subtype of stroke with high disability and high mortality with no effective treatment modality. The predilection site of ICH is in the area of basal ganglia and internal capsule (IC), where exist abundant white matter (WM) fiber bundles, such as cerebrospinal tract (CST) in the IC. Asproximal or distal white matter injury (WMI) caused by bleeding within the brain parenchyma is highly associated with poor prognosis after ICH, especially motor and sensory functional deficit. The pathophysiological mechanisms involved in WMI are quite complex and still far from clear. In recent years, the neuroprotection and repairment capacity of mesenchymal stem cells (MSCs) has been widely investigated after ICH. MSCs exert many unique biological effects including self-recovery by produced growth factors and cytokine, regenerative repair, immunomodulation, neuroprotection against oxidative stress, etc., which provides a promising cell therapy in the WMI. Taken together, our goal is to discuss the characteristics of WMI following ICH, including the mechanism and potential promising therapeutic targets of MSCs, in the hope that this may shed new light on the future treatment strategies.